2018
DOI: 10.1371/journal.pone.0195162
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of DNMT1 in vertebrates: Duplications in marsupials followed by positive selection

Abstract: DNA methylation is mediated by a conserved family of DNA methyltransferases (Dnmts). The human genome encodes three active Dnmts (Dnmt1, Dnmt3a and Dnmt3b), the tRNA methyltransferase Dnmt2, and the regulatory protein Dnmt3L. Despite their high degree of conservation among different species, genes encoding Dnmts have been duplicated and/or lost in multiple lineages throughout evolution, indicating that the DNA methylation machinery has some potential to undergo evolutionary change. However, little is known abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…In silico analysis of DNA methylation genes in the present study showed that only one dnmt1 gene was fixed in the genomes of most species in chordates, which was in accordance with previous studies 34,35 . A recent study concerning the molecular evolution of dnmt1 in vertebrates demonstrated that an additional SSD event occurred before the radiation of major marsupial groups, giving rise to the fixation of two dnmt1 copies in marsupials 11 . www.nature.com/scientificreports www.nature.com/scientificreports/ Here, we also identified two dnmt1 genes in trout and salmon, which were supposed to arise from the SaGD thus being ohnologous genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico analysis of DNA methylation genes in the present study showed that only one dnmt1 gene was fixed in the genomes of most species in chordates, which was in accordance with previous studies 34,35 . A recent study concerning the molecular evolution of dnmt1 in vertebrates demonstrated that an additional SSD event occurred before the radiation of major marsupial groups, giving rise to the fixation of two dnmt1 copies in marsupials 11 . www.nature.com/scientificreports www.nature.com/scientificreports/ Here, we also identified two dnmt1 genes in trout and salmon, which were supposed to arise from the SaGD thus being ohnologous genes.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA methylation/demethylation machinery has been well described in mammals. While dnmt1 is generally identified as single-copy gene during evolution 11 , multiple dnmt3 genes were found in vertebrates with different gains and losses among tetrapod lineages 12 . The mammalian dnmt3 family consists of four members: dnmt3a, dnmt3b, dnmt3c and dnmt3l 13,14 .…”
mentioning
confidence: 99%
“…Gene duplication is one of the evolutionary approaches that permit versatile advancement in genomes. It has been revealed for other proteins that positive selection happens after a duplication event that proposes an unwinding of the selective pressure supporting genetic variation [49,50]. This relaxation was missing not only in avian but also in other vertebrates' lineages during PD1 evolution, conferring to the Bayesian phylogenetic approaches ( Supplementary Figure 10).…”
Section: Agingmentioning
confidence: 96%
“…It remains unclear whether marsupial X chromosomes undergo similar differential DNA methylation. Interestingly, marsupial genomes harbor an additional copy of DNMT1, the gene encoding the DNA methyltransferase responsible for DNA methylation maintenance (Leonhardt, et al 1992;Goll and Bestor 2005), through gene duplication (Alvarez-Ponce, et al 2018), which could lead to functional divergence between the mammalian lineages. Several previous studies found little difference in DNA methylation between active and inactive marsupial X chromosomes (Piper, et al 1993;Loebel and Johnston 1996;Wang, et al 2014).…”
Section: Introductionmentioning
confidence: 99%